Arsenite: the umpire of arsenate perception and responses in plants. (May 2022) - Kandhol, Nidhi; Singh, Vijay Pratap; Herrera-Estrella, Luis; Tran, Lam-Son Phan; Tripathi, Durgesh Kumar
Abstract : Arsenite regulates the uptake and detoxification of arsenate in plants under low-phosphate conditions by governing the stability of PHOSPHATE STARVATION RESPONSE 1, as reported in a recent study by Navarro and colleagues . This finding opens new opportunities for research into developing mitigation strategies to deal with arsenic toxicity in plants.